Influence of GSTP-1 Polymorphism on the Prognosis of Patients with High-Grade Glioma Who Received Temozolomide Plus Radiotherapy Adjuvant Treatment - Zhi DB; Wang ZY; Xie T; Tu WW (International Journal of General Medicine, 2021)
De-Bao Zhi,1,* Zhi-Yu Wang,2,* Tong Xie,1 Wen-Wen Tu1 1Department of Surgical Care Unit, Xuhui District Central Hospital, Shanghai, 200031, People’s Republic of China; 2Department of Neurosurgery, Xuhui District Central Hospital, Shanghai, 200031, People’s Republic of China*These authors contributed equally to this workCorrespondence: De-Bao Zhi Tel +86 18616568331Email zhidebao@163.comBackground: Glutathione S-Transferase P 1 (GSTP-1) gene plays an important physiological role in the body. The present study was conducted to identify the clinical implication of GSTP-1 gene polymorphism on the prognosis of patients with high-grade glioma (HGG) who received temozolomide plus radiotherapy adjuvant treatment.Methods: This study recruited a total of 186 patients with HGG who were treated with temozolomide plus radiotherapy adjuvant regimen (retrospectively). Baseline clinical characteristics were obtained and the prognostic data of the patients were collected. Peripheral blood specimen of patients was preserved for genotyping of GSTP-1 polymorphism during hospitalization. Correlation analysis was carried out accordingly. Additionally, fresh peripheral blood specimens that were available for mRNA expression analysis were collected for the mRNA expression analysis.Results: The median progression-free survival (PFS) and overall survival (OS) of the 186 patients with HGG who received temozolomide plus radiotherapy regimen was 8.5 months (95% CI: 5.95– 11.05) and 15.5 months (95% CI: 11.49– 19.51), respectively. The prevalence of 313A>G among 186 patients with glioma was AA genotype: 126 cases (67.7%), AG genotype: 54 cases (29.1%), GG genotype: 6 cases (3.2%), minor allele frequency of 313A>G was 0.18. Association analysis suggested that the median PFS of patients with AA and AG/GG genotypes was 11.2 and 5.0 months, respectively (χ2=11.17, P=0.001). Furthermore, the median OS of patients with AA and AG/GG genotypes was 18.9 and 10.5 months, respectively (χ2=12.684, P< 0.001). Besides, when adjusted for PFS in multivariate Cox regression analysis, AG/GG genotype was an independent factor for PFS (HR=0.48, P=0.006). The mRNA expression results indicated that mRNA expression of GSTP-1 in patients with AG/GG genotypes of 313A>G was significantly higher than that of patients with AA genotype (P< 0.001).Conclusion: GSTP-1 polymorphism 313A>G might be used as a potential biomarker to predict the prognosis of patients with HGG who received temozolomide plus radiotherapy adjuvant treatment.Keywords: high-grade glioma, temozolomide, GSTP-1, polymorphism, prognosis